2020
DOI: 10.1007/s00415-020-09838-9
|View full text |Cite
|
Sign up to set email alerts
|

Serum phosphorylated neurofilament heavy-chain levels reflect phenotypic heterogeneity and are an independent predictor of survival in motor neuron disease

Abstract: To investigate the prognostic role and the major determinants of serum phosphorylated neurofilament heavy -chain (pNfH) concentration across a large cohort of motor neuron disease (MND) phenotypes. Enzyme-linked immunosorbent assay (ELISA) was used to measure serum pNfH concentration in 219 MND patients consecutively enrolled in our tertiary MND clinic. A multifactorial analysis was carried out to investigate the major clinical determinants of serum pNfH. Kaplan-Meier survival curves and Cox regression analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 40 publications
1
28
0
Order By: Relevance
“…In univariate regression models, NF levels retain a high hazard risk for death [57,70,81]. More importantly, in multivariate models encompassing all other known prognostic factors such as ALSFRS-r, site of onset, age at onset, weight loss, and respiratory measures, only serum NfL concentration and some clinical variable different from one study to another (FVC [90] age, baseline ALSFRS-R, ΔFRS [86]), resulted as independent predictors of survival [90,91]. Considering ALSFRS-R slope as the outcome, and taking into account baseline serum NfL and pNfH together with potential clinical predictors of prognosis (age, sex, C9ORF72 status, site of disease onset, baseline ALSFRS-R and ΔFRS), only progression rate resulted a meaningful clinical predictor.…”
Section: Nfs As Prognostic Biomarkers In Als and Other Mndsmentioning
confidence: 96%
See 2 more Smart Citations
“…In univariate regression models, NF levels retain a high hazard risk for death [57,70,81]. More importantly, in multivariate models encompassing all other known prognostic factors such as ALSFRS-r, site of onset, age at onset, weight loss, and respiratory measures, only serum NfL concentration and some clinical variable different from one study to another (FVC [90] age, baseline ALSFRS-R, ΔFRS [86]), resulted as independent predictors of survival [90,91]. Considering ALSFRS-R slope as the outcome, and taking into account baseline serum NfL and pNfH together with potential clinical predictors of prognosis (age, sex, C9ORF72 status, site of disease onset, baseline ALSFRS-R and ΔFRS), only progression rate resulted a meaningful clinical predictor.…”
Section: Nfs As Prognostic Biomarkers In Als and Other Mndsmentioning
confidence: 96%
“…Other studies supported the use of baseline serum or CSF NfL levels as an independent prognostic factor, with equal, if not superior value, of progression rate at diagnosis (delta-FS) [71], one of the most widely accepted clinical prognostic index computed at diagnosis [83]. A recent study showed significantly higher serum pNfH concentration in pyramidal, bulbar, and classic phenotypes (with the lowest concentrations in flail arm ALS, PMA, and PLS) and in more advanced cases (King's stages 3 and 4 compared to King's 1 and 2), with a positive correlation between pNfH and progression rate suggesting that a faster degeneration of the motor system is one of the determinants of serum pNfH concentration [91].…”
Section: Nfs As Prognostic Biomarkers In Als and Other Mndsmentioning
confidence: 99%
See 1 more Smart Citation
“…Candidate biomarkers are an area of active research to exploit CSF or serum elements which may provide better diagnostic and/or prognostic assessments of neurodegenerative disease, including motor neuron spectrum disorders. Both neurofilament light chains (NfL) and phosphorylated neurofilament heavy chains (pNfH) can be measured in serum and in CSF and have been shown to be correlated with disease severity and survival parameters in motor neuron disease [ 66 , 67 ]. The mechanism underlying their elevation (UMN degeneration versus LMN degeneration) continues to be a matter of debate.…”
Section: Diagnosticsmentioning
confidence: 99%
“…This is supported by lower comparative values in pure UMN degeneration syndromes such as PLS or HSP as compared to classic ALS, although, diagnostic cut-offs have yet to be clearly defined [ 68 , 69 , 70 , 71 ]. Alternatively, recent studies have found higher levels of CSF NfL and serum pNfH chains in typical ALS as well as those with UMNdALS and pseudobulbar palsy as compared to those syndromes that primarily affect the lower motor neurons such as progressive muscular atrophy or the flail arm/leg syndromes [ 66 , 67 ]. These findings along with the known elevated levels (serum or CSF) of NfL or pNfH in ALS as compared to PLS or HSP may suggest that the rate of degeneration of the corticospinal tract drives the differences between these disorders [ 66 , 67 , 72 , 73 ].…”
Section: Diagnosticsmentioning
confidence: 99%